2022
DOI: 10.1038/s41524-022-00897-2
|View full text |Cite
|
Sign up to set email alerts
|

A public database of thermoelectric materials and system-identified material representation for data-driven discovery

Abstract: Thermoelectric materials have received much attention as energy harvesting devices and power generators. However, discovering novel high-performance thermoelectric materials is challenging due to the structural diversity and complexity of the thermoelectric materials containing alloys and dopants. For the efficient data-driven discovery of novel thermoelectric materials, we constructed a public dataset that contains experimentally synthesized thermoelectric materials and their experimental thermoelectric prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…One of the fundamental goals in thermoelectric materials is to discover novel materials of high ZT . To this end, various calculation and machine learning methods have been proposed to predict ZTs of the materials from their chemical compositions. ,, Although existing methods successfully predicted ZTs from the chemical compositions of the thermoelectric materials, they overlooked the effect of the synthesis process on the thermoelectric properties of the materials. Various experimental observations showed that the energy conversion efficiency changes by different synthesis processes even if product materials have the same chemical composition. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fundamental goals in thermoelectric materials is to discover novel materials of high ZT . To this end, various calculation and machine learning methods have been proposed to predict ZTs of the materials from their chemical compositions. ,, Although existing methods successfully predicted ZTs from the chemical compositions of the thermoelectric materials, they overlooked the effect of the synthesis process on the thermoelectric properties of the materials. Various experimental observations showed that the energy conversion efficiency changes by different synthesis processes even if product materials have the same chemical composition. , …”
Section: Resultsmentioning
confidence: 99%
“…For data-driven research on material synthesis, we constructed a benchmark dataset that contains 771 unique thermoelectric materials and their synthesis processes by extracting experimentally validated synthesis recipes from the scientific literature in the ESTM dataset. 35 We collected the materials synthesis recipes of the thermoelectric materials based on ChemDataExtractor 26 with human supervision. In this paper, we refer to the collected dataset as the thermoelectric materials synthesis recipes (TMSR) dataset.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(3) Rapidly hot-pressing and sintering the obtained powder into samples. In this study, a dataset of GeTe-based thermoelectric materials, as reported in previous literature, 33 was selected. This dataset consists of 458 samples, with each sample comprising the chemical formula, temperature, and ZT value.…”
Section: Materials and Establishment Of Datasetmentioning
confidence: 99%
“…19 Along the lines of StarryData2, Na and Chang constructed a dataset containing 5205 chemical compositions of the experimentally synthesized thermoelectric materials and their experimental thermoelectric properties. 20 All these approaches rely on manual or semi-manual extraction from the literature. Sierepeklis and Cole used a combination of web-scrapping and natural language processing to develop the first automatically generated database of thermoelectric materials and their properties from the existing literature, containing 22 805 data records, automatically generated from the scientific literature, spanning 10 641 unique extracted chemical names.…”
Section: Introductionmentioning
confidence: 99%